2010
DOI: 10.3736/jcim20100108
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between constitutional types of traditional Chinese

Abstract: Phlegm-dampness, yin deficiency, and qi deficiency constitutions are the main influential factors of hypertension. Hypertensive patients with different gender have different constitutional influential factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…People of balanced constitution have better quality of life than those of imbalanced constitution [9]. Moreover, imbalanced constitution seemed to have strong correlation with chronic diseases such as obesity [10] and hypertension [11]. …”
Section: Introductionmentioning
confidence: 99%
“…People of balanced constitution have better quality of life than those of imbalanced constitution [9]. Moreover, imbalanced constitution seemed to have strong correlation with chronic diseases such as obesity [10] and hypertension [11]. …”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have identified that different TCM constitution is predisposed to certain diseases. For instance, individuals with yin-deficiency and phlegmdampness constitutions tend to suffer from hypertension [24,25], while those with yang-deficiency constitution are more easily attacked by osteoporosis [26,27]. erefore, it makes contributions to alleviate disease burdens through identifying influential factors of biased constitutions and adjusting human body towards balanced constitution.…”
Section: Discussionmentioning
confidence: 99%
“…TCMCs are relatively stable and adjustable, and acquired factors greatly in uence the development of individual TCMC over time [5][6][7]. According to the TCM theory, individual unbalanced constitutions have a higher susceptibility to certain diseases than balanced constitutions that have been con rmed by several investigators [8][9][10]. Understanding TCMC and its in uencing factors are necessary for generating guidance for an individual's health protection and preventing diseases.…”
Section: Introductionmentioning
confidence: 99%